Aplikasi Sistem Informasi Geografis Pencarian Rumah Sakit dan Puskesmas dengan Algoritma Djiktra Berbasis Android - Mutammimul Ula; Rayhan Rahul Mutuahmi; Sayed Fachrurrazi; Reyhan Achmad Rizal; Ilham Sahputra (STMIK Budi Darma, 2023)
The application that was built can see the entire location of the hospitals and health centers in Lhokseumawe. The designed system can also provide information about hospitals and health centers, with an android application. This application can also help medical personnel and users to see the location and address of each hospital and health center. The method in this study is to make observations in determining the addresses of hospitals and health centers that are spread from various points in the city of Lhokseumawe. then data analysis techniques by identifying emerging themes in the form of locations and categories according to the search themes addressing the intended location. The purpose of this study was to find out the location of hospitals and health centers in the city of Lhokseumawe and can serve as a medium of information regarding data on hospitals and health centers in the city of Lhokseumawe. The results obtained are an android-based hospital and puskesmas data collection information system application in the city of Lhokseumawe. The contribution of this research, users can see the intended route and the application displays the direction of the road being passed. then the user can see the road that is passed based on android and the success rate of the application that is running is very good. The next result of this research is that the user can see the intended route from the Lilawangsa Kesrem Hospital, Tumpok Teungoh to the Kasih Ibu Foundation Hospital, Jalan Merdeka Timur, Kutabalng, and the total distance that must be traveled is 1.12. As for the Keude Cunda Metro Medical Center RSU to Dr. Hanafiah Hasan Hospital, Jalan Darusslam, Kampung Jawa Lama, with a total distance of 4.07 km. The contribution of this research, users can see the intended route and the application displays the direction of the road being passed. then the user can see the road that is passed based on android and the success rate of the application that is running is very good. The next result of this research is that the user can see the intended route from the Lilawangsa Kesrem Hospital, Tumpok Teungoh to the Kasih Ibu Foundation Hospital, Jalan Merdeka Timur, Kutabalng, and the total distance that must be traveled is 1.12. As for the Keude Cunda Metro Medical Center RSU to Dr. Hanafiah Hasan Hospital, Jalan Darusslam Kampung Jawa Lama with a total distance of 4.07 km.